Efektivitas penggunaan poster dan video dalam meningkatkan pengetahuan dan sikap tentang buah dan sayur pada siswa Dayah Terpadu Inshafuddin - Jellyfa Indah; Junaidi Junaidi (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: The World Health Organization (WHO) generally recommends the consumption of vegetables and fruit for a healthy life of 400 grams per person per day, consisting of 250 grams of vegetables and 150 grams of fruit. Not all Indonesians consume fruits and vegetables as much as 97.3% consume vegetables 73.6% consume fruit, nutrition education with audio-visual media is effective in increasing students' knowledge.Objective: This study aims to measure the effectiveness of poster and video media in increasing students' knowledge and attitudes about fruits and vegetables at Dayah Terpadu Inshafuddin.Methods: This study used a quasi-experimental research design (quasi-experimental). The sample in this study was all students of class 2A and 2C Dayah Terpadu Inshafuddin Banda Aceh, with the study time in 2019. Data collection used a questionnaire and direct interviews were conducted. The data is processed using computer applications. Data analysis using T-dependent and T-independent tests.Results: The results showed that students' knowledge of vegetables and fruit increased to 83.6%, and attitudes increased to 84.5%. There was an increase in students' knowledge and attitudes about fruits and vegetables between before and after counseling (p < 0.05). In addition, it also showed that there was a significant effect of counseling using videos and posters (p < 0.05).Conclusion: The use of posters and video media can increase students' knowledge and attitudes, and using video media is more effective than posters in increasing knowledge and attitudes about vegetable and fruit consumption.